Menu Close

x-f-i-x-i-f-i-u-f-i-u-i-f-i-u-x-a-h-proved-that-x-a-hu-




Question Number 214448 by jahar last updated on 08/Dec/24
  x^−  = ((Σf_i x_i )/(Σf_i  )) ,   u^−  = ((Σf_i u_i )/(Σf_i )) , u = ((x−a)/h) ,  proved that x^−  = a + hu^−
$$ \\ $$$$\overset{−} {{x}}\:=\:\frac{\Sigma{f}_{{i}} {x}_{{i}} }{\Sigma{f}_{{i}} \:}\:,\:\:\:\overset{−} {{u}}\:=\:\frac{\Sigma{f}_{{i}} {u}_{{i}} }{\Sigma{f}_{{i}} }\:,\:{u}\:=\:\frac{{x}−{a}}{{h}}\:, \\ $$$${proved}\:{that}\:\overset{−} {{x}}\:=\:{a}\:+\:{h}\overset{−} {{u}} \\ $$

Leave a Reply

Your email address will not be published. Required fields are marked *